2007
DOI: 10.1002/jsfa.2858
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified atmosphere and vacuum packaging on microbial, chemical and sensory quality indicators of fresh, filleted Sardina pilchardus at 3 °C

Abstract: The self-life, quality and safety of refrigerated sardine fillets (Sardina pilchardus) were determined at 3• C in atmospheric air, vacuum and modified atmosphere (50% CO 2 /50% N 2 ) packaging conditions. Microbiological, physico-chemical and sensory parameters were utilised as quality indicators. The microbial flora of sardine comprised -according to order of occurrence -Shewanella putrefaciens, pseudomonads, Brochothrix thermosphacta, lactic acid bacteria and, finally, Enterobacteriaceae. Bacteria grew most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 42 publications
3
28
2
2
Order By: Relevance
“…A rapid increase in fillets was observed after 3 days of storage and reached 4.49 ± 0.02 log cfu/g on day 9 (Table 7). Stamatis and Arkoudelos (2007), reported that initial populations of LAB were 1.8 log cfu/g, while a count of more than 7 log cfu/g did not exceed in all different packing conditions for filleted S. pilchardus at 3 o C. H 2 S bacteria which is important by spoilage process was reported as 1.89 ± 0.20 log cfu/g for fresh meagre samples and showed increases after storing. According to gutting process, it increased to 5.54 (A), 6.51 (B), 5.49 (C) and 7.51 log cfu/g (D) on 9 days of storage (Table 8).…”
Section: Microbiological Analyse Resultsmentioning
confidence: 89%
“…A rapid increase in fillets was observed after 3 days of storage and reached 4.49 ± 0.02 log cfu/g on day 9 (Table 7). Stamatis and Arkoudelos (2007), reported that initial populations of LAB were 1.8 log cfu/g, while a count of more than 7 log cfu/g did not exceed in all different packing conditions for filleted S. pilchardus at 3 o C. H 2 S bacteria which is important by spoilage process was reported as 1.89 ± 0.20 log cfu/g for fresh meagre samples and showed increases after storing. According to gutting process, it increased to 5.54 (A), 6.51 (B), 5.49 (C) and 7.51 log cfu/g (D) on 9 days of storage (Table 8).…”
Section: Microbiological Analyse Resultsmentioning
confidence: 89%
“…Air-stored hake slice showed higher TVC than MAP (50% CO 2 /45% N 2 /5% O 2 ) stored hake after 2 days of iced storage (Pastoriza et al, 1998). Bacteria grew more quickly in sardines stored in air, followed by those in vacuum packaging, and the lowest counts were found in sardine stored under MAP (Stamatis & Arkoudelos, 2007). Storage at low temperature in combination with the presence of 60% CO 2 inhibited both TVC and psychrophilic bacterial growth in smoked trout fillets stored at 4°C (Sukran, Berna, Tolga, & Sebnem, 2006).…”
Section: Effect Of Tannic Acid In Combination Without and With Map Onmentioning
confidence: 85%
“…It has been confirmed that fish packaging in modified atmosphere significantly extends the shelf life of the product (Masniyom et al 2002;Stamatis & Arkoudelos 2007;Provincial et al 2010). The most common freshwater fish retailed in the Serbia are carp.…”
mentioning
confidence: 87%